Prototype of a multi-user chaos-based system with correlator and support vector machine receivers - Berber, Stevan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Multiuser communication techniques are used in modern wireless networks like cellular and wireless sensor networks. The design of the physical layer for these networks was based on the application of binary spreading sequences and a correlation receiver. This paper presents a design of a multiuser code division transceiver using a new method of communication based on the application of chaotic spreading sequences that can increase security of the system, and on a new technique of detecting the received signal using a support vector machine and a traditional correlation receiver. The two receivers are theoretically analyzed, including the derivation of the probability of error expression in a closed form for the fading channel, and then implemented in DSP technology on a 32-bit floating-point TigerSHARC DSP platform. The comparison of two implemented systems showed that the support vector machine solution improves the robustness of the system, sacrificing the speed of processing. The achievable bit rate for the correlator receiver was up to two times higher than for the support vector machine receiver.